Inflation and Deflationary Biases in Inflation Expectations - Michael Lamla; Damjan Pfajfar; Lea Rendell (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We explore the consequences of losing confidence in the price-stability objective of central banks by quantifying the inflation and deflationary biases in inflation expectations. In a model with an occasionally binding zero-lower-bound constraint, we show that an inflation bias as well as a deflationary bias exist as a steady-state outcome. We assess the predictions of this model using unique individual-level inflation expectations data across nine countries that allow for a direct identification of these biases. Both inflation and deflationary biases are present (and sizable) in inflation expectations of these individuals. Among the euro-area countries in our sample, we can document significant differences in perceptions of the European Central Bank's objectives, despite having a common monetary policy.
Keywords: E31; E37; E58; D84; 330; inflation bias; deflationary bias; confidence in central banks; trust; ZLB; inflation; expectations; microdata